Design, Formulation, and Evaluation of Novel Dissolving Microarray Patches Containing Rilpivirine for Intravaginal Delivery. Issue 9 (6th March 2019) - Mc Crudden, Maelíosa T. C.; Larrañeta, Eneko; Clark, Annie; Jarrahian, Courtney; Rein‐Weston, Annie; Creelman, Benjamin; Moyo, Yolanda; Lachau‐Durand, Sophie; Niemeijer, Nico; Williams, Peter; McCarthy, Helen O.; Zehrung, Darin; et al.
Abstract: Antiretroviral (ARV) drugs have, for many years, been studied and administered in the prevention and treatment of human immunodeficiency virus (HIV). Intramuscular (IM) injection of long acting (LA) ARVs are in clinical development, but injectable formulations require regular access to healthcare facilities and disposal facilities for sharps. The development of a discrete, self‐administered, and self‐disabling vehicle to deliver ARVs could obviate these issues. This study describes the formulation, mechanical characterization, and in vivo evaluation of dissolving microarray patches (MAPs) containing a LA nanosuspension of the ARV, rilpivirine (RPV, RPV LA), for vaginal delivery. This is the first study to apply MAPs into vaginal tissue. The RPV LA MAPs penetrate ex vivo skin and a synthetic vaginal skin model and withstand the effects of potential dragging motion across synthetic vaginal epithelium. In in vivo studies, the mean plasma concentration of RPV in rats at the 56 day endpoint (116.5 ng mL −1 ) is comparable to that achieved in the IM control cohort (118.9 ng mL −1 ). RPV is detected systemically, in lymph and vaginal tissue, indicating the potential to deliver RPV LA to primary sites of viral challenge and replication. This innovative research has future potential for patients and healthcare workers, particularly in low‐resource settings. Abstract : A study describing the design, formulation and characterisation of novel dissolving microarray patches (MAP) for vaginal delivery of a long acting nanosuspension of the antiretroviral (ARV) drug, rilpivirine (RPV). In an in vivo model, RPV is detected systemically, in lymph and vaginal tissue. This innovative delivery system could have wide ranging benefits for patients and healthcare workers in the future.